Small molecule inhibitor against onco-mucins disrupts Src/FosL1 axis to enhance gemcitabine efficacy in pancreatic ductal adenocarcinoma. (28th December 2022) - Zhang, Chunmeng; Atri, Pranita; Nallasamy, Palanisamy; Parte, Seema; Rauth, Sanchita; Nimmakayala, Rama Krishna; Marimuthu, Saravanakumar; Chirravuri-Venkata, Ramakanth; Bhatia, Rakesh; Halder, Sushanta; Shah, Ashu; Cox, Jesse L.; et al.
Abstract: Mucin MUC4 is an aberrantly expressed oncogene in pancreatic ductal adenocarcinoma (PDAC), yet no pharmacological inhibitors have been identified to target MUC4. Here, we adapted an in silico screening method using the Cancer Therapeutic Response Database (CTRD) to Identify Small Molecule Inhibitors against Mucins (SMIMs). We identified Bosutinib as a candidate drug to target oncogenic mucins among 126 FDA-approved drugs from CTRD screening. Functionally, Bosutinib treatment alone/and in combination with gemcitabine (Gem)/5′ fluorouracil (5FU) reduced in vitro viability, migration, and colony formation in multiple PDAC cell lines as well as human PDAC organoid prolifertaion and growth and in vivo xenograft growth. Further, biochemical and molecular analyses showed that Bosutinib exhibited these functional effects by downregulating MUC4 mucin at both transcript and translation levels in a dose- and time-dependent manner. Mechanistically, global transcriptome analysis in PDAC cells upon treatment with Bosutinib revealed disruption of the Src-ERK/AKT-FosL1 pathway, leading to decreased expression of MUC4 and MUC5AC mucins. Taken together, Bosutinib is a promising, novel, and highly potent SMIMs to target MUC4/MUC5AC mucins. This mucin-targeting effect of Bosutinib can be exploited in the future with cytotoxic agents to treat mucinous tumors. Highlights: Mucins are major players and less explored therapeutically in pancreatic cancer. Among mucins, MUC4 is highly expressed and associated with pancreatic cancer. Computational analysis of FDA-approved drug screening for Mucins revealed Bosutinib to block MUC4 and MUC5AC. Bosutinib enhances gemcitabine efficacy by blocking SRC-AKT/ERK-FosL1 axis in pancreatic cancer cells. Combined utilization of MUC4-specific targeting of small molecule inhibitors improved gemcitabine efficacy.